Using RAPD markers for genetic analysis in Three Species of Datura in Iraq - Lubna Amir Altiaee; Akeel H ALassi; Thammer A. Zahwan (Tikrit Journal of Pure Science)
The study amis to develop the evidence genetic of active substances for several kinds of the Datura plant (Datura sp.), So it was procedure steps to isolated the Genomic DNA from leaf of Datura specis    it is (Datura metel, Datura innoxia and Datura stramonium).(